Perbaikan Kemampuan Biomotorik Pesepakbola Usia Dini Melalui Suplementasi Zn+Fe - Taiyeb, Abdul Mushawwir; Patellongi, Ilhamjaya (bionature, 2008)
The research aimed to examine the effect of Zn+Fe supplementation on optimalizing the biomotoric ability. One field intervention research among of 40 of a 12-years old group of football players of Makassar Football School (MFS)-2000 in South Sulawesi Province had been conducted to figure out a possible mechanism specifically examined the discrapancies of the change in the increasing rate of biomotoric ability between the targeted and the placebo group. This study was designed with randomized double blind pretest-posttest. A full of 20 participants in group A (targeted group) was supple-mented by Zn+Fe for 6 months while other 20 in group B counterparts were given with placebo. All data related to biometric ability, nutrient supplementation, hemoglobin level as well as IGF-1 level were recorded before and after intervention. The result showed greater increasing in the level of Hb, IGF-1, biomotoric ability: muscle endurance (sit-up test), and aerobic endurance (bleep test) among the targeted group up  to 2.05%, 32,5%, 19.85% and 47.08% respectively, after supplemented by Zn+Fe for 6 months, compared to that number in the placebo group (0.61%; 15%; 5.11% and 11,66% respectively). Moreover, the result demonstrated a positive correlation between the level of Hb and the increasing of ability to perform sit-up (r= 0.361) as well as aerobic capacity (r= 0.325). Similar result found in correlation between IGF-1 and the increasing rate of ability to perform sit-up (r= 0.385) as well as aerobic capacity (r= 0.392). Conclusions, the increasing level of Hb and IGF-1 improved the increasing rate of, muscle endurance in sit-up test as well as aerobic endurance in bleep test. Therefore, giving Zn+Fe supplementation may improvement biomotoric ability in  12-years old group of football players.   Keywords: biomotoric  ability, Zn + Fe supplementation, nutrition feed, fitness tests